A Multidisciplinary and a Comprehensive Approach to Reducing Fragility Fractures in Preterm Infants - Saif, Saif A.; Maghoula, Mohammad; Babiker, Amir; Abanmi, Mashael; Nichol, Fiona; Al Enazi, Modhi; Guevarra, Elenor; Sehlie, Faisal; Al Shaalan, Hesham; Mughal, Zulf (Current Pediatric Reviews, 2024)
With advances in neonatal care, bone fractures prior to discharge from the hospital in preterm infants receiving contemporary neonatal care, are rare. Nevertheless, such fractures do occur in very low birth weight and extremely low birth weight infants who go on to develop metabolic bone disease of prematurity (MBDP), with or without secondary hyperparathyroidism. MBDP is a multifactorial disorder arising from the disruption of bone mass accrual due to premature birth, postnatal immobilisation, and loss of placental oestrogen resulting in bone loss, inadequate provision of bone minerals from enteral and parenteral nutrition, and medications that leach out bone minerals from the skeleton. All of these factors lead to skeletal demineralisation and a decrease in bone strength and an increased risk of fractures of the long bones and ribs. Secondary hyperparathyroidism resulting from phosphate supplements, or enteral/parenteral feeds with a calcium-tophosphate ratio of < 1.3:1.0 leads to subperiosteal bone resorption, cortical thinning, and further skeletal weakening. Such fractures may occur from routine handling and procedures such as cannulation. Most fractures are asymptomatic and often come to light incidentally on radiographs performed for other indications. In 2015, we instituted a comprehensive and multidisciplinary Neonatal Bone Health Programme (NBHP), the purpose of which was to reduce fragility fractures in high risk neonates, by optimising enteral and parenteral nutrition, including maintaining calcium-tophosphate ratio ≥1.3:1, milligram to milligram, biochemical monitoring of MBDP, safe-handling of at-risk neonates, without compromising passive physiotherapy and skin-to-skin contact with parents. The at-risk infants in the programme had radiographs of the torso and limbs at 4 weeks and after 8 weeks from enrolment into the program or before discharge. Following the introduction of the NBHP, the bone fracture incidence reduced from 12.5% to zero over an 18-month period.
Keywords: parathyroid hormone